Employing arynes in multicomponent reactions and rearrangements triggered by nitrogen nucleophiles - Roy, T. (CSIR-National Chemical Laboratory, Pune, 2019)
The thesis is about the Employment of Arynes in Multicomponent Reactions and Rearrangements Triggered by Nitrogen Nucleophiles
Keywords: Multicomponent Reactions; Rearrangements